P235 Localizing non-epileptic abnormal brain function in children using high density EEG (HDEEG): Electric source imaging (ESI) of focal slowing. Issue 9 (September 2017) - Baldini, Sara; Coito, Ana; Korff, Christian; Schaller, Karl; Seeck, Margitta; Pittau, Francesca; Vulliemoz, Serge
Abstract : Objectives: Interictal focal slowing is an important EEG index of brain activity dysfunction, possibly representing an additional tool for presurgical evaluation in pediatric epilepsy. Here, we investigate the accuracy of electric source imaging (ESI) applied to pathological focal EEG slowing (FS) as new neurophysiological index localizing the epileptic focus in children with drug-resistant epilepsy. Method: We selected16 children (12 ± 4yrs), who performed hdEEG, presurgical evaluation and underwent surgical resection with at least 1 year of post-operative seizure freedom. For each patient, we exported 15 FS-epochs of 2 s. The S-transform was applied to select the frequency band (delta/theta: 1–4 Hz/4–8 Hz) with maximal power. ESI was performed using a distributed linear inverse solution and an individual head model. The solution point with maximal average power in the band of interest was selected as the source of focal slowing (ESI-FS). Finally, we computed the Euclidian distance between the ESI-FS and the nearest solution point included in the resection with a 5 mm margin. Results: In 11/16 (69%), ESI of focal slowing (ESI-FS) was inside the margins of resection. The remaining 5/16 cases had distances < 15 mm. Discussion and Conclusions: These findings suggest that a "non-epileptiform" activity, such as focal slowing, could help to localize the epileptogenic zone. ESI-FS may aid presurgical lateralization in patients without focal interictal spikes improving the identification of possible good candidate for surgical treatment. Significance: The study provides a new quantitative marker of brain dysfunction in children, with a potential application to other neurological disorders, using a non-invasive tool as hdEEG.